Buddhist Tourism : The Pattern and Network Tourism Management of The Temples In Thai Society - Jayānuvaddho, Phra Srisungkom; Valaisathien, Parichart (Mahachula Academic Journal, 2020)
This academic article contains 3 objectives: (1) to study the Buddhist tourism Pattern (2) to study the role of promotion and linkage of meditation practice network of the temple and (3) to analyze the role of promotion and the link of meditation practice of temple and its tourism network management. This was a qualitative survey by observing and interviewing 10 monks who live at tourist temple and then analyzing the data synthesized to write in descriptive style. The results revealed that Buddhist tourism in Thai society was divided into 2 types: (1) the temples which promote Buddhist art works, merit performances, blessings that are organized as inside and outside environment according to each temple’s context. There is religious symbols using and simple communication which is a very popular from past to present ( 2) the temple that promotes meditation place which is well-known by both Thai and foreign tourists. The temples that promote Buddhist arts revealed that they while promoted merit activities in every auspicious day of Buddhism and nation, culture will applies meditation and Vipassana practice in order to encourage suitability tourists. It builds up a link to direct their minds further in meditation in temples that promote continuous practice of meditation. The results of temple’s model and roles showed that the temple that has followed rightly practice as Dharma practice network throughout Thai society contains 2 levels of management: (1) policy level or the highest Buddhist administration organization of the Thai Sangha called Sangha Supreme Council of Thailand (SSC), with the committee of Buddhism propagation responsible for dharma practice. The committee raised various projects to promote, support and encourage the Dharma network to form the standard teaching of meditation practice for efficiency by using the correct teaching based on Mahāsati- paṭṭhānasutta (2) operator level signifying an in charge who manages their temple and other branch of temple to be proper and ready to develop Vipassana teachers for long and well settlement of Buddhism. Although there are increasing of tourists who had appreciated the Buddhist arts and interested almost are adults and seniors but only small number of youth were seen therefore the government agencies and Buddhist organizations should have given right understanding, promote and support tourism to develop the mind by allowing the youth to perform their leaderships and participate Buddhist tourism activities as much as possible.